Silicon carbide-based Janus membrane as well as preparation method and application thereof
By air sintering and hydrophobic modification on the silicon carbide separation layer, a silicon carbide-based Janus film with superhydrophobic/hydrophilic asymmetric Janus structure was prepared, which solved the problems of low flux and easy contamination in the existing membrane, and achieved efficient membrane distillation application and long-term use.
Patent Information
- Application Number
- CN202510330370.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-03-20
AI Technical Summary
The existing silicon carbide hydrophobic membranes have problems such as uncontrollable pore size, high mass transfer resistance and easy contamination in membrane distillation applications, resulting in low membrane flux and short service life.
By air sintering technology is used to regulate the silicon carbide separation layer, and superhydrophobic/hydrophilic asymmetric Janus structure is introduced, and hydrophobic modification is carried out in combination with graft polymerization to prepare a silicon carbide-based Janus film with controllable pore size.
The membrane flux is significantly improved, the mass transfer resistance is reduced, and the flux can be restored through a simple cleaning procedure when membrane fouling occurs, extending the service life of the filter membrane.
Smart Images

Figure CN119896975A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional membrane preparation, and relates to a silicon carbide-based Janus membrane and a preparation method and application thereof. Background Art
[0002] The increasing scarcity of freshwater resources has become a global challenge, and seawater desalination is seen as an effective way to solve this problem. Among the many seawater desalination technologies, membrane distillation has attracted widespread attention due to its advantages such as low energy consumption, compact system design and simple operation.
[0003] However, in the commercialization process of membrane distillation, there are still some long-standing and prominent problems that need to be improved, such as membrane scaling, pore wetting and low permeability flux of its core component hydrophobic membrane. Research on these issues is currently mainly focused on organic membrane materials. Patent CN107511081B provides a method for preparing an anti-pollution PTFE-CA / SiNPs composite membrane, and particularly relates to a method for preparing a composite membrane with surface oil resistance and porous three-dimensional spatial network structure by electrospinning. The invention constructs a super-hydrophilic anti-pollution layer on the surface of the hydrophobic base membrane PTFE by electrospinning to prepare a PTFE-CA / SiNPs composite membrane. The method has a simple film-forming process, convenient operation, and is easy to realize industrial production; and the prepared composite membrane has good anti-pollution performance, high permeability flux, strong chemical stability, good mechanical properties, high interception efficiency, and has broad application prospects. Patent CN115463554A discloses a method for preparing a PVDF-HFP / TPU multi-level structure nanofiber membrane by electrospinning and its membrane distillation application, which belongs to the field of membrane distillation technology. The preparation method is to use polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and thermoplastic polyurethane (TPU) as spinning polymer raw materials, and prepare a multi-level nanofiber composite membrane through electrostatic spinning technology. PVDF-HFP nanofiber membrane has excellent hydrophobic properties and low crystallinity; TPU has superior comprehensive performance, flexibility, toughness and antibacterial properties, and its unique hard and soft segment microphase structure allows the presence of hydrophilic groups and hydrophobic groups on the molecular chain segments, and has good moisture permeability. By using electrostatic spinning technology to mix different proportions of TPU into the PVDF-HFP spinning solution, the hydrophilic groups in the membrane pores are modified, and a high-throughput, mechanically strong multi-level nanofiber composite membrane can be prepared. The composite membrane prepared by the invention shows high permeation flux, interception rate and long-term stability in the membrane distillation process, and has broad application prospects in water treatment fields such as seawater desalination and brackish water.
[0004] However, the membranes provided by the above patents have some disadvantages: first, the bonding strength between the hydrophobic layer and the hydrophilic layer of the membrane is weak, and the mechanical properties are still poor compared to ceramic membranes, resulting in a short service life. Secondly, the hydrophobic angle of the membrane is low, and membrane wetting is prone to occur. In addition, the high porosity and nanofiber structure are prone to adsorb organic matter, microorganisms or colloidal particles, resulting in membrane pollution.
[0005] In recent years, hydrophobic ceramic membranes have gradually attracted great attention due to their long service life and have been used in vacuum membrane distillation (VMD), oil-in-water emulsion separation, CO 2 It has been applied in scenarios such as capture and waste heat recovery. Among them, porous silicon carbide ceramic membrane is a new type of ceramic membrane that has gradually developed in recent years. It has the advantages of high flux, strong anti-fouling ability, acid and alkali resistance, and corrosion resistance. At present, hydrophobically modified silicon carbide ceramic membranes have been used in oil-water emulsion separation. For example, the literature (Y. Wang, C. Yuan, K. Zhou, Q. Gu, W. Jing, Z. Zhong, W. Xing, Construction of Janus silicon carbidemembranes with asymmetric wettability for enhanced antifouling in water-in-oil emulsification process [J]. Journal of Membrane Science, 2023, 671: 121389) uses silane coupling agent to hydrophobically modify one side of the pure silicon carbide membrane to prepare a SiC membrane with asymmetric wettability. The membrane can separate small-sized W / O emulsions and has good anti-fouling ability and renewability. However, the application of pure silicon carbide hydrophobic membranes in membrane distillation has not yet been reported.
[0006] Research has found that the limited application of silicon carbide ceramic membranes in membrane distillation may be mainly attributed to two factors: First, the scarcity of functional groups on the surface of silicon carbide makes it difficult to achieve a stable and strong hydrophobic modification effect. Second, the pore size of silicon carbide membranes is larger than that of inorganic membranes such as alumina, resulting in a low retention rate for materials in membrane distillation applications. Preparing a silicon dioxide-bonded silicon carbide separation layer through air sintering technology and then performing hydrophobic modification is a feasible solution.
[0007] Air sintering is to sinter silicon carbide in an air atmosphere and form a silicon carbide separation layer bonded with silicon dioxide on the surface. This method has been proposed and proved in the applicant's previous patent (CN115845619A) that it can effectively reduce the sintering temperature of silicon carbide, and the separation layer obtained has a higher mechanical integrity and a smaller pore size, and the silicon carbide separation layer bonded with silicon dioxide obtained by this method is both firm and conducive to hydrophobic modification. However, the hydrophobic modification method of this patent is relatively complicated and fails to reach a super-hydrophobic state. At the same time, the prepared membrane is a full hydrophobic membrane and has a smaller pore size, resulting in an increase in mass transfer resistance, thereby making the membrane distillation flux lower. In addition, the membrane also has the problem of faster pollution and difficulty in cleaning of scaling, which shortens its service life. Therefore, it is urgent to develop a super-hydrophobic membrane with a controllable pore size, lower mass transfer resistance and easy to clean, so as to improve the membrane distillation flux and extend the service life of the filter membrane. Summary of the invention
[0008] In view of the current situation in the prior art that there is a lack of a super-hydrophobic membrane with controllable pore size, low mass transfer resistance and easy cleaning, the present invention provides a silicon carbide-based Janus membrane and a preparation method and application thereof.
[0009] This application is based on the air sintering technology in the previous patent (CN115845619A), and has made key improvements in both separation layer pore size control and hydrophobic modification.
[0010] First, the pore size of the separation layer was regulated, and the membrane flux was increased by about 2 times while maintaining the vacuum membrane distillation retention rate (>99%). Secondly, a super-hydrophobic / hydrophilic asymmetric Janus structure was creatively introduced, which not only improved the membrane flux to a certain extent, but also, when membrane fouling occurred during operation, the flux could be restored through a simple cleaning procedure, thus extending the service life of the filter membrane.
[0011] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0012] One of the technical solutions of the present application provides a method for preparing a silicon carbide-based Janus film, comprising the following steps:
[0013] a) preparing a silicon carbide separation layer slurry; coating the silicon carbide separation layer slurry on one side of a silicon carbide support to obtain a single-sided coated silicon carbide blank; and air-sintering the single-sided coated silicon carbide blank to obtain a silicon dioxide-bonded silicon carbide-based ceramic membrane;
[0014] b) Then, the silicon dioxide-bonded silicon carbide-based ceramic membrane obtained in step a) is subjected to single-sided hydrophobic modification by a graft polymerization method to obtain a silicon carbide-based Janus membrane.
[0015] Furthermore, the preparation of the silicon carbide separation layer slurry in step a) is prepared by ball milling, the steps of: mixing silicon carbide powder, binder, dispersant and RO water in a mass ratio of (5-15): (0.05-0.15): (1-2): (80-90), and grinding in a ball mill;
[0016] Furthermore, the particle size of the silicon carbide powder in step a) is (4-6) μm, preferably 5 μm; the ball milling time is 1-5 hours, preferably 2.5 hours; the binder is selected from any one of hydroxypropyl methylcellulose, methyl cellulose or sodium hexametaphosphate; the dispersant is selected from any one of polyethylene glycol, polyvinyl alcohol and polyacrylic acid.
[0017] Furthermore, there are two particle sizes in the silicon carbide separation layer slurry prepared in step a), the small particle size is 59-220nm, and the large particle size is 342-1032nm, and the particle size and the content of the large and small particles are determined by the ball milling time; the solid content of the slurry in step a) is 5-15wt%, preferably 10wt%;
[0018] Furthermore, the coating in step a) is preferably performed by using an ultrasonic spray coating method to deposit the silicon carbide separation layer slurry on a single side of the silicon carbide support.
[0019] Furthermore, the purpose of the air sintering in step a) is to bond the deposited particles to the silicon carbide support to obtain a silicon carbide-based ceramic membrane bonded with silicon dioxide; the air sintering is preferably carried out in a muffle furnace; the air sintering adopts the following process:
[0020] ① First, in an air atmosphere, heat from room temperature to 300°C at a heating rate of 5°C / min, and then keep at 300°C for 15 to 25 minutes;
[0021] ② Then in air atmosphere, heat from 300°C to 600°C at a heating rate of 5°C / min, and then keep at 600°C for 15 to 25 minutes;
[0022] ③ Then in air atmosphere, heat from 600°C to 800°C at a heating rate of 5°C / min, and then keep at 800°C for 15 to 25 minutes;
[0023] ④ Then in air atmosphere, heat from 800°C to 1100-1300°C at a heating rate of 5°C / min;
[0024] ⑥ Sintering at 1100-1300℃ in air atmosphere for 2 hours;
[0025] ⑦Finally, cool naturally to room temperature in air atmosphere.
[0026] Further, in a specific embodiment of the present application, step b) includes the following specific operations:
[0027] b1) preparing a 1H,1H,2H,2H-perfluorooctyltrichlorosilane (FOTS) solution and stirring the solution evenly;
[0028] b2) spraying the FOTS solution prepared in step b1) on the separation layer side and drying to obtain a silicon carbide-based Janus membrane.
[0029] Furthermore, the solvent of the 1H,1H,2H,2H-perfluorooctyltrichlorosilane (FOTS) solution in step b1) is any one of n-hexane, cyclohexane, hexadecane, and anhydrous ethanol, preferably n-hexane; the mass fraction of the FOTS solution is 0.4-1.6 vol%, preferably 1 vol%; and the stirring time is 15-25 min.
[0030] Furthermore, the 1H,1H,2H,2H-perfluorooctyltrichlorosilane (FOTS) can be replaced by other silane coupling agents, and the specific operation methods may be different.
[0031] Furthermore, the drying in step b2) is preferably carried out in a vacuum drying oven; the drying temperature is 100-200° C. and the drying time is 0.5-1.5 hours.
[0032] Furthermore, the principle of the grafting polymerization method involved in this step is as follows: FOTS is hydrolyzed in n-hexane solvent to generate silanol, which undergoes a condensation reaction with the hydroxyl-rich silicon dioxide-bonded silicon carbide separation layer to form Si-O-Si covalent bonds, and at the same time, the silanol molecules are laterally cross-linked to form a dense and ordered perfluoroalkyl monolayer.
[0033] The second technical solution of the present application provides a silicon carbide-based Janus membrane obtained by the above technical solution. The silicon carbide-based Janus membrane is based on a silicon carbide support body, and a super-hydrophobic silicon carbide separation layer is sprayed on one side; the pore size of the silicon carbide-based Janus membrane is 100nm to 1000nm; the pure water flux is 1418.82 to 4405.82kg / (m 2 h).
[0034] The hydrophobic angle of the membrane separation layer under the preferred conditions (air sintering temperature of 1200°C; 1 vol% FOTS solution) is 151.33°; the side of the support body not sprayed with the separation layer maintains excellent hydrophilicity, and water droplets can be completely immersed in a short time (0.12s). The silicon carbide-based Janus membrane has outstanding acid and alkali resistance, friction resistance and thermal stability.
[0035] The third technical solution of the present application provides the application of the silicon carbide-based Janus membrane obtained by the above technical solution. The silicon carbide-based Janus membrane is used to prepare a membrane module to achieve membrane distillation of seawater and convert seawater into desalinated water.
[0036] In the vacuum membrane distillation application with 3.5wt% NaCl solution as the feed solution, the silicon carbide-based Janus membrane exhibits a high membrane flux, and the membrane flux can be restored to about 90% after simple cleaning. In addition, when the NaCl solution containing supersaturated gypsum is used as the feed solution, the membrane flux change trend of the silicon carbide-based Janus membrane is basically consistent with that of the NaCl solution without gypsum, indicating that the silicon carbide-based Janus membrane has excellent anti-scaling properties.
[0037] Compared with the prior art, the present invention has the following significant beneficial effects:
[0038] The super-hydrophobic / hydrophilic Janus membrane prepared in this application not only has an excellent super-hydrophobic separation layer and a hydrophilic support, but also has excellent performance in acid and alkali resistance, friction resistance, thermal stability and anti-scaling performance, and the membrane distillation flux is significantly improved. At the same time, the present invention uses a simple cleaning method so that the membrane flux can maintain a 90% recovery rate in the VMD long-term cycle experiment. Therefore, the super-hydrophobic / hydrophilic composite Janus filter membrane prepared by this method has an efficient and environmentally friendly application prospect for seawater desalination. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 is a phase comparison diagram of the silicon dioxide bonded silicon carbide separation layer and the silicon carbide support characterized by XRD in Example 1;
[0040] Figure 2 1 is a scanning electron microscope image of the silicon dioxide bonded silicon carbide film at different sintering temperatures in Example 2, wherein Figures (a), (c), and (e) are silicon dioxide bonded silicon carbide films sintered at 1100° C., 1200° C., and 1300° C., respectively; Figures (b), (d), and (f) are corresponding partial enlarged images, respectively;
[0041] Figure 3 is the particle gradation in the slurry liquid at different ball milling times in Example 3;
[0042] Figure 4 is a pore size distribution diagram of the silicon dioxide bonded silicon carbide membrane measured by different methods in Example 3, wherein Figure 4 (a) and (b) are mercury intrusion methods. Figure 4 (c) is the fluorescent probe method;
[0043] Figure 5It is a physical picture of the silicon carbide support, silicon dioxide bonded silicon carbide film and silicon carbide based Janus film;
[0044] Figure 6 is the wettability characterization of the silicon carbide-based Janus film in Example 4; Figure 6 (a) Wetting of silicon carbide-based ceramic membrane using 4 μL RO water droplets as the test liquid; Figure 6 (b) is the FTIR analysis results of silicon carbide-based ceramic membrane samples before and after modification;
[0045] Figure 7 The stability of the silicon carbide-based Janus film prepared in Example 4 is explored; Figure 7 (a) is the change of hydrophobic angle of SiC-based Janus film after heat treatment at 100℃, 120℃, 150℃ and 200℃; Figure 7 (b) is the contact angle measurement using RO water, sulfuric acid (pH = 1) and sodium hydroxide (pH = 13) as the test liquid; Figure 7 (c) is the change of hydrophobic angle of silicon carbide-based Janus film before and after sandpaper wear test;
[0046] Figure 8 is the hydrophobic angle of the silicon carbide-based Janus membrane at different modifier concentrations in Example 5;
[0047] Fig. 9 The comparison of the membrane distillation treatment effect of the silicon carbide-based Janus membrane and the double-sided hydrophobic modified silicon carbide-based ceramic membrane on salt water in Example 6;
[0048] Fig.10 In Example 7, the effects of the silicon carbide-based ceramic membranes with three pore sizes prepared in Example 3 after being modified with reference to Example 4 in the membrane distillation test were compared;
[0049] Fig.11 is a comparison of the membrane flux variation trends of the silicon carbide-based Janus membrane when the salt solution containing gypsum and the salt solution without gypsum are used as the feed solution in Example 8;
[0050] Fig.12 The diagram is the change in membrane flux and conductivity over time during the VMD long-term desalination test of the silicon carbide-based Janus membrane in Example 9 after the membrane is cleaned using the cleaning process in Example 6. DETAILED DESCRIPTION
[0051] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is described in detail below in conjunction with specific embodiments. It should be noted that the following embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any form. It should be noted that for those of ordinary skill in the art, several variations and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0052] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0053] Example 1 A silicon carbide-based ceramic membrane bonded with silicon dioxide
[0054] In this embodiment, a silicon carbide-based ceramic membrane bonded with silicon dioxide is prepared, and the specific steps are as follows:
[0055] a1) 5 μm silicon carbide powder (Shandong Sailike Membrane Technology Co., Ltd.), hydroxypropyl methylcellulose (Shandong Sailike Membrane Technology Co., Ltd.), polyethylene glycol (Shandong Sailike Membrane Technology Co., Ltd.) and RO water (reverse osmosis water) were mixed in a mass ratio of 10:0.1:1.4:88.5 and added to a planetary ball mill, and then a planetary ball mill (3S-T10, Beijing Tonglin Technology Co., Ltd.) was used, with silicon carbide balls as the ball milling medium, and the ball-to-material ratio was controlled to be 5:1, and the ball milling speed was 380 rpm, and the ball milling was performed for 2.5 hours to obtain a silicon carbide separation layer slurry liquid, and the slurry liquid-solid content was 10 wt%;
[0056] The slurry was ultrasonically sprayed on a silicon carbide support (Shandong Sailico Membrane Technology Co., Ltd.) using an ultrasonic thin film spraying device (UAM4000E, Hangzhou Chifei Ultrasonic Equipment Co., Ltd.); during ultrasonic spraying, the stage temperature was 90°C, the spraying pressure was 0.4MPa, the ultrasonic frequency was 40kHz, the spraying flow rate was 1.9mm / s, the number of spraying times was 20 times, and the thickness of the silicon carbide separation layer was controlled to be 31±2μm; then it was placed in a vacuum drying oven (DZF-6050, Shanghai Huitai Instrument Manufacturing Co., Ltd.) and dried at 100°C for 4 hours to obtain a single-sided coated silicon carbide blank;
[0057] a2) placing the dried single-sided coated silicon carbide blank prepared in step a1) into a muffle furnace (KSL-1400X-A1, Hefei Kejing Material Technology Co., Ltd.) for air sintering to obtain a silicon dioxide-bonded silicon carbide-based ceramic membrane; the air sintering adopts the following process:
[0058] ① First, in an air atmosphere, heat from room temperature to 300°C at a heating rate of 5°C / min, and then keep at 300°C for 20 minutes;
[0059] ② Then in air atmosphere, heat from 300°C to 600°C at a heating rate of 5°C / min, and then keep at 600°C for 20 minutes;
[0060] ③ Then in air atmosphere, heat from 600°C to 800°C at a heating rate of 5°C / min, and then keep at 800°C for 20 minutes;
[0061] ④ Then in air atmosphere, heat from 800°C to 1200°C at a heating rate of 5°C / min;
[0062] ⑥ Sintering at 1200℃ in air atmosphere for 2 hours;
[0063] ⑦Finally, cool naturally to room temperature in air atmosphere.
[0064] The silicon dioxide-bonded silicon carbide-based ceramic membrane obtained above was characterized:
[0065] Figure 1 The figure shows the phase contrast of the silicon dioxide bonded silicon carbide separation layer and the silicon carbide support characterized by XRD. Figure 1 As shown, the characteristic peaks of the silicon dioxide bonded silicon carbide separation layer and the silicon carbide support body are highly overlapped, and there is only a difference in the characteristic peaks between 20 and 25 degrees at 2θ angles. The comparison of PDF card PDF#27-0605 shows that the characteristic peaks between 20 and 25 degrees at 2θ angles are amorphous silicon dioxide, indicating that the prepared ceramic membrane is a silicon dioxide bonded silicon carbide membrane.
[0066] Example 2 Investigation of the sintering temperature of silicon carbide-based ceramic membranes bonded with silicon dioxide
[0067] This example adopts the method described in Example 1, except that the air sintering temperature is adjusted from 1200°C to 1100°C and 1300°C; then the separation layer firmness and pure water flux of the silicon dioxide-bonded silicon carbide-based ceramic membrane are tested at the three sintering temperatures.
[0068] The specific method of testing the firmness is as follows: first, inject 50 mL of ultrapure water into a beaker, and then place a 2 The membrane separation layer was placed flat on the bottom of the beaker with the membrane separation layer facing downward. The beaker was then placed in an ultrasonic cleaning machine (KQ-3200, Kunshan Ultrasonic Instrument Co., Ltd.) and ultrasonicated for 5 minutes at a power of 100 kW. After the treatment was completed, the solution was fully mixed and its turbidity value was measured using a turbidity meter (2100N, Hach Company, USA).
[0069] The pure water flux is tested using a self-built dead-end filtration system (routine operation by those skilled in the art). The specific test method is: assemble the membrane sample in a well-sealed mold, then open the pressure regulating valve to accurately control the filtration pressure at 1 bar. The filtrate mass change is recorded in real time by a high-precision electronic balance (ME204EJ02, Mettler-Toledo Instruments Shanghai Co., Ltd.), and calculated according to the flux formula. The calculation formula for pure water flux J is: J = M / (A×t); Where: J: pure water flux, the unit is usually kg / (m 2 h MPa) (kilograms per square meter per hour per megapascal); M: the mass of pure water passing through the membrane, in kilograms (kg); A: the effective area of the membrane, in square meters (m 2 );t: filtering time, in hours (h).
[0070] Figure 2 The following are scanning electron microscope images of silicon dioxide bonded silicon carbide based ceramic membranes at different sintering temperatures. Figure 2 (a), (c), and (e) are silicon dioxide-bonded silicon carbide-based ceramic membranes sintered at 1100°C, 1200°C, and 1300°C, respectively. Figure 2 (b), 2(d), and 2(f) are the corresponding partial enlarged images. Figure 2 It can be seen that the separation layer is smooth and defect-free, and the fine particles are combined together by forming silica. Moreover, with the increase of sintering temperature, the particles in the separation layer gradually become rounded and more sintering necks are formed between the particles, which gradually increases the bonding strength between the particles in the separation layer.
[0071] Table 1 shows the turbidity and pure water flux data of silicon dioxide bonded silicon carbide-based ceramic membranes after ultrasound at different sintering temperatures. The turbidity of the sample sintered at 1100°C reached 283.9 NTU after ultrasound, which is much higher than the membranes at the other two sintering temperatures. This shows that the separation layer formed under low sintering temperature conditions has poor firmness, causing serious surface powder shedding. The pure water flux of the sample sintered at 1300°C is only 1418.82±153.61 kg / (m 2 h), which is much lower than the other two sintering temperatures. This is because the viscous flow of silicon dioxide is enhanced at this sintering temperature, forming a dense silicon dioxide film, which increases the gas-liquid permeation resistance. Therefore, 1200°C was selected as the sintering temperature of silicon dioxide bonded silicon carbide film in subsequent experiments.
[0072] Table 1 Post-ultrasonic turbidity and pure water flux at different sintering temperatures
[0073] Sintering temperature Turbidity (NTU) <![CDATA[Pure water flux (kg / (m 2 ·h))]]> 1100℃ 283.9 4405.82±924.4 1200℃ 56.56 3523.3±311.54 1300℃ 19.86 1418.82±153.61
[0074] Example 3 Investigating the effect of ball milling time on the particle size distribution of slurry and the pore size of silicon dioxide bonded silicon carbide-based ceramic membrane
[0075] This example adopts the method described in Example 1, except that the ball milling time of 2.5 h in the method for preparing the silicon carbide separation layer slurry is adjusted to 2 h and 3 h; then the particle gradation of the three slurries is detected, and the mercury intrusion method is used (for specific operations, please refer to the literature: Y. Liu, Q. Jiang, K. Zhou, Q. Gu, Z. Zhong, W. Jing, Y. Fan, W. Xing, Tailored surface wettability and pore structure of hydrophobic SiO 2 / SiC membranes forpreparing monodisperse emulsion with high-efficiency,Applied Surface Science2024,665:160364) and the fluorescence probe method (for specific operations, please refer to the literature: J.Zhu, J.Wang, H.Zhong, Y.Hu, L.Hu, P.Rao, R.Liu, J.Zhu, G.Li, New method for measuring the pore sizes and poresize distributions of filter membranes—the fluorescence probe method,Microchim Acta, 2023, 190(12):469) were used to measure the pore sizes of three silica-bonded silicon carbide-based ceramic membranes.
[0076] Figure 3 The particle gradation in the slurry liquid under different ball milling times is shown. It can be seen that with the increase of ball milling time, the large particles gradually decrease and the fine particles increase.
[0077] Figure 4 (a) and 4(b) show the pore size distribution diagrams of the silicon carbide support and the silicon dioxide bonded silicon carbide-based ceramic membrane measured by the mercury injection method. The pore size of the silicon carbide support is about 6600nm, while for the silicon dioxide bonded silicon carbide membrane prepared at different ball milling times, the pore size of the separation layer decreases with the increase of ball milling time. Figure 4 (c) The same conclusion was obtained by the fluorescent probe method (449nm~331nm). The pore size of the silicon dioxide-bonded silicon carbide-based ceramic membrane prepared by this method is between 100nm and 1000nm, which is in line with the application pore size requirements of membrane distillation.
[0078] Example 4 A Silicon Carbide-Based Janus Membrane
[0079] The silicon dioxide-bonded silicon carbide-based ceramic membrane prepared in Example 1 was subjected to the following hydrophobic modification:
[0080] b1) using n-hexane as solvent, preparing a 1 vol% 1H,1H,2H,2H-perfluorooctyltrichlorosilane (FOTS) solution, and vigorously stirring it with a magnetic stirrer (84-1A6S, Shanghai Silo Instrument Co., Ltd.) for 20 min;
[0081] b2) The cleaned silica-bonded silicon carbide-based ceramic membrane support side is completely covered with tape, and the FOTS solution prepared in step b1) is sprayed on the separation layer side using a spray bottle, and then placed in a vacuum drying oven at 150° C. for 1 hour to obtain a silicon carbide-based Janus membrane that can be used for membrane distillation.
[0082] The silicon carbide support used in Example 1, the silicon dioxide bonded silicon carbide film prepared in Example 1, and the silicon carbide-based Janus film provided in Example 4 are shown in the following figures. Figure 5 shown.
[0083] The wettability of the silicon carbide-based Janus membrane obtained in this example was characterized, and the contact angle of the membrane material was detected using a drop shape analyzer (DSA30S, Krues, Germany). The specific measurement process is as follows: Use a micro-syringe to accurately drop 4 μL of test droplets on the horizontally placed membrane surface. After the droplets are stable, the droplet morphology is captured by the built-in high-speed camera system of the instrument, and the contact angle value is calculated using the supporting analysis software. The characterization results are as follows:
[0084] Figure 6 It is a characterization of the wettability of SiC-based Janus films. Figure 6 (a) is the wetting condition of the silicon carbide-based ceramic membrane using 4 μL RO water droplets as the test liquid. Through detection, it was found that the contact angle of the modified side (separation layer) of the silicon carbide-based Janus membrane prepared in this embodiment to water can be stabilized at more than 150°, while the contact angle of the unmodified side (support body) can be completely immersed in a short time (0.12 s), indicating that the hydrophilicity is still maintained well. Figure 6 (b) shows the FTIR analysis results of the silicon carbide-based ceramic membrane samples before and after modification. The 1240 cm -1 There is an absorption peak near 3 -characteristic peaks, while the silicon dioxide-bonded silicon carbide-based ceramic membrane before modification did not show the corresponding functional groups, indicating that the FOTS modification was successful.
[0085] Figure 7 This paper studies the stability of the prepared silicon carbide-based Janus membrane. Figure 7As shown in (a), the hydrophobic angle of the SiC-based Janus membrane did not change significantly after heat treatment at 100°C, 120°C, 150°C, and 200°C for 10 hours. Figure 7 (b) shows the contact angle measurements using RO water, sulfuric acid (pH = 1), and sodium hydroxide (pH = 13) as the test liquids. Within 10 minutes, the WCA values of the three test liquids decreased by 7.59°, 7.12°, and 10.93°, respectively. The main reason for the decrease in contact angle may be due to the volatilization of the liquid. In addition, the change in the hydrophobic angle of the silicon carbide-based Janus film before and after the sandpaper wear test was characterized. Figure 7 As shown in (c), after 30 reciprocating wear cycles, the WCA only decreases by about 10°. The experimental results show that the hydrophobic separation layer of the silicon carbide-based Janus membrane prepared in this embodiment has good thermal stability, acid and alkali resistance, and wear resistance.
[0086] Example 5 Investigating the effect of modifier concentration on the hydrophobicity of the obtained silicon carbide-based Janus membrane
[0087] This example adopts the method described in Example 4, except that the mass fraction of the 1H,1H,2H,2H-perfluorooctyltrichlorosilane (FOTS) solution is adjusted from 1 vol% to 0.4 vol% to 1.6 vol%.
[0088] The hydrophobic angle of the membrane under different modifier concentrations is as follows Figure 8 Under the same conditions, with the increase of modifier concentration, the contact angle of the modified side of the silicon carbide-based Janus membrane first increased and then decreased, indicating that 1 vol% is the optimal concentration for graft polymerization, which can make the contact angle of the hydrophobic membrane to water as high as 151.33°.
[0089] Comparative Example 1 A double-sided hydrophobic modified silicon dioxide bonded silicon carbide based ceramic membrane
[0090] This example adopts the modification method described in Example 4, except that the FOTS solution is sprayed on both the separation layer side and the support body side instead of spraying only the FOTS solution on the separation layer side in step b2). After the modification, the contact angle on the separation layer side is 150.67°, and the contact angle on the support body side is 147.48°. It can be seen that under the same conditions, the hydrophobicity of the obtained membrane is better when the FOTS solution is sprayed only on the separation layer side.
[0091] Example 6 Membrane distillation test of silicon carbide-based Janus membrane
[0092] The silicon carbide-based Janus membrane prepared in Example 4 and the double-sided hydrophobic modified silica-bonded silicon carbide-based ceramic membrane prepared in Comparative Example 1 were used for membrane distillation testing.
[0093] The test conditions of membrane distillation are as follows: 1) 3.5% NaCl solution; 2) feed liquid flow rate is 0.225 m / s; 3) temperature is 80° C.; 4) single test time is 1 hour.
[0094] After the membrane distillation test was completed, the membrane was cleaned using the following cleaning procedure: first, the pipeline was cleaned with 500 mL of 80 °C deionized water, then the feed side and the permeate side were exchanged, and a vacuum membrane distillation process was performed with 80 °C deionized water for 1 h, and finally the filter membrane was dried.
[0095] Then the membrane distillation treatment effects of two different hydrophobic ceramic membranes on salt water were compared by using two indicators: membrane flux and salt retention rate. Fig. 9 As shown; wherein: the membrane flux is determined by the mass of the distillate; the salt retention rate is determined by the conductivity of the solution before and after distillation (conductivity method, a conventional measurement method in the art).
[0096] Depend on Fig. 9 The results show that the initial membrane flux of the silicon carbide-based Janus membrane prepared in Example 4 is higher, and the membrane flux can be restored by about 90% after cleaning. This shows that the membrane can not only be used for membrane distillation applications, but also has a significant membrane distillation effect and has obvious application value.
[0097] Example 7 Investigating the effect of the pore size of the silicon dioxide bonded silicon carbide separation layer on the membrane distillation effect
[0098] The silicon dioxide-bonded silicon carbide-based ceramic membranes with three pore sizes prepared in Example 3 were modified according to Example 4 and used for membrane distillation test. The results are as follows: Fig.10 As shown in the figure. The salt rejection rate of the filter membrane with an average pore size of 967nm in the separation layer is only 7.13%, indicating that the membrane with this pore size is not enough to withstand the vacuum membrane distillation operating conditions. Compared with the other two filter membranes, the membrane flux of the filter membrane with an average pore size of 810nm in the separation layer is much higher than that of the filter membrane with an average pore size of 601nm while ensuring the salt rejection rate.
[0099] Example 8 Investigation of the anti-scaling performance of the silicon carbide-based Janus membrane prepared by the method of the present invention
[0100] This example adopts the method described in Example 6, except that the 3.5% NaCl solution is replaced by a solution containing supersaturated gypsum (CaSO 4 , 20 mM) NaCl solution;
[0101] like Fig.11 As shown in the figure, the membrane flux decline trend of the silicon carbide-based Janus membrane when the feed solution is a salt solution containing gypsum is basically the same as that of the salt solution without gypsum, and the salt rejection rate reaches 99.9%. This shows that the silicon carbide-based Janus membrane has excellent anti-scaling properties.
[0102] Example 9 Investigating the long-term stability of the silicon carbide-based Janus membrane prepared by the method of the present invention in vacuum membrane distillation applications
[0103] This example adopts the VMD method described in Example 6, except that the operating time is changed from 1 hour to membrane cleaning after every 6 hours of continuous operation.
[0104] Fig.12 The changes of membrane flux and salt rejection rate over time of the silicon carbide-based Janus membrane during the vacuum membrane distillation long-term desalination test are shown after the membrane is cleaned using the cleaning process in Example 6. It can be seen that after each membrane cleaning cycle, the membrane flux can be restored to more than 90% relative to the initial flux, and the salt rejection rate is also maintained at 99%, indicating that no membrane pore wetting occurs during the entire operation. The above experimental results show that the silicon carbide-based Janus membrane with a layered structure can improve the desalination performance and anti-wetting properties in the vacuum membrane distillation process, and the vacuum membrane distillation process only needs a simple pure water cleaning process after each run.
[0105] In summary, it can be seen that the present invention successfully prepared a silicon carbide-based ceramic membrane with controllable pore size by adopting an oxidative sintering method, and prepared a super-hydrophobic / hydrophilic composite Janus ceramic membrane by a graft polymerization method, and successfully applied it to a desalination test based on a vacuum membrane distillation method. This method not only obtains a super-hydrophobic silicon carbide-based ceramic membrane, but also has excellent acid and alkali resistance, friction resistance, thermal stability and anti-scaling properties, while achieving high flux in membrane distillation applications while ensuring the interception rate. At the same time, a simple cleaning method was used, so that the membrane flux could maintain a 90% recovery rate in the VMD long-term cycle experiment. It is proved that the super-hydrophobic / hydrophilic composite Janus ceramic membrane prepared by this method has a prospect for efficient and environmentally friendly seawater desalination applications.
[0106] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a silicon carbide-based Janus film, characterized in that: The steps include: a) preparing a silicon carbide separation layer slurry; coating the silicon carbide separation layer slurry on one side of a silicon carbide support to obtain a single-sided coated silicon carbide blank; and air-sintering the single-sided coated silicon carbide blank to obtain a silicon dioxide-bonded silicon carbide-based ceramic membrane; b) Then, the silicon dioxide-bonded silicon carbide-based ceramic membrane obtained in step a) is subjected to single-sided hydrophobic modification by a graft polymerization method to obtain a silicon carbide-based Janus membrane.
2. The method for preparing a silicon carbide-based Janus film according to claim 1, characterized in that: The preparation of the silicon carbide separation layer slurry in step a) is prepared by ball milling, and the steps are: mixing silicon carbide powder, binder, dispersant and RO water in a mass ratio of (5-15): (0.05-0.15): (1-2): (80-90) and grinding.
3. The method for preparing a silicon carbide-based Janus film according to claim 2, characterized in that: Step a) The particle size of the silicon carbide powder is 4 to 6 μm; the ball milling time is 1 to 5 hours; the binder is selected from any one of hydroxypropyl methylcellulose, methyl cellulose or sodium hexametaphosphate; and the dispersant is selected from any one of polyethylene glycol, polyvinyl alcohol and polyacrylic acid.
4. The method for preparing a silicon carbide-based Janus film according to claim 2, characterized in that: There are two particle sizes in the silicon carbide separation layer slurry prepared in step a), the small particle size is 59-220nm, and the large particle size is 342-1032nm; the solid content of the slurry in step a) is 5-15wt%.
5. The method for preparing a silicon carbide-based Janus film according to claim 1, characterized in that: The air sintering in step a) adopts the following process: ① First, in an air atmosphere, heat from room temperature to 300°C at a heating rate of 5°C / min, and then keep at 300°C for 15 to 25 minutes; ② Then in air atmosphere, heat from 300°C to 600°C at a heating rate of 5°C / min, and then keep at 600°C for 15 to 25 minutes; ③ Then in air atmosphere, heat from 600°C to 800°C at a heating rate of 5°C / min, and then keep at 800°C for 15 to 25 minutes; ④ Then in air atmosphere, heat from 800°C to 1100-1300°C at a heating rate of 5°C / min; ⑥ Sintering at 1100-1300℃ in air atmosphere for 2 hours; ⑦Finally, cool naturally to room temperature in air atmosphere.
6. The method for preparing a silicon carbide-based Janus film according to claim 1, characterized in that: Step b) includes the following specific operations: b1) preparing 1H,1H,2H,2H-perfluorooctyltrichlorosilane solution and stirring it evenly; b2) spraying the 1H,1H,2H,2H-perfluorooctyltrichlorosilane solution prepared in step b1) on the separation layer side and drying to obtain a silicon carbide-based Janus membrane.
7. The method for preparing a silicon carbide-based Janus film according to claim 6, characterized in that: In step b1), the solvent of the 1H,1H,2H,2H-perfluorooctyltrichlorosilane solution is any one of n-hexane, cyclohexane, hexadecane and anhydrous ethanol; the mass fraction of the 1H,1H,2H,2H-perfluorooctyltrichlorosilane solution is 0.4-1.6 vol%; and the stirring time is 15-25 min.
8. The method for preparing a silicon carbide-based Janus film according to claim 6, characterized in that: The drying temperature in step b2) is 100-200° C. and the drying time is 0.5-1.5 hours.
9. A silicon carbide-based Janus film obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The silicon carbide-based Janus membrane is based on a silicon carbide support body, and a super-hydrophobic silicon carbide separation layer is sprayed on one side; the pore size of the silicon carbide-based Janus membrane is 100nm-1000nm; the pure water flux is 1418.82-4405.82kg / (m 2 h).
10. The use of a silicon carbide-based Janus film according to claim 9, characterized in that: The silicon carbide-based Janus membrane is used to prepare a membrane module to achieve membrane distillation of seawater and convert seawater into desalinated water.
Citation Information
Patent Citations
A method for preparing an antifouling PTFE-CA / SiNPs composite membrane
CN107511081B
Preparation method of multistage nanofiber composite membrane for membrane distillation
CN115463554A
Hydrophobic material permeability composite material, preparation method thereof and use thereof
CN101423617A
Method for hydrophobic modification of porous ceramic membrane and application of porous ceramic membrane in membrane distillation
CN108380058A
Preparation method of silicon carbide asymmetric composite filter tube membrane with controllable aperture, and device
CN109867524A
Cited By
Tubular silicon carbide ultrafiltration membrane based on controllable filling method and preparation method thereof
CN121466803A